ic-Separation Axioms in Topological Spaces - Beyda S. Abdullah; Ruqayah N. Balo; Sabih W. Askandar (Academic Science Journal)
A new class of separation axioms known as ic-separation axioms is introduced in this study. They rely on new extended open sets known as ic-open sets, and we describe the relationship between them and give several examples. Additionally, we define ic-generalized closed set concepts in a topological space in order to frame the another class of separation axioms called ic-generalized  axioms. Among other things, the basic concern properties and relative preservation properties of these spaces are projected under ic-generalized irresolute mappings.